Flexible energy-saving strategies in female temperate-zone bats - Keicher, Lara; Shipley, J. Ryan; Komar, Ewa; Ruczyński, Ireneusz; Schaeffer, Paul J.; Dechmann, Dina K. N. (Zenodo, 2022)
(Uploaded by Plazi for the Bat Literature Project) Torpor is characterized by an extreme reduction in metabolism and a common energy-saving strategy of heterothermic animals. Torpor is often associated with cold temperatures, but in the last decades, more diverse and flexible forms of torpor have been described. For example, tropical bat species maintain a low metabolism and heart rate at high ambient and body temperatures. We investigated whether bats (Nyctalus noctula) from the cooler temperate European regions also show this form of torpor with metabolic inhibition at high body temperatures, and whether this would be as pronounced in reproductive as in non-reproductive bats. We simultaneously measured metabolic rate, heart rate, and skin temperature in non-reproductive and pregnant females at a range of ambient temperatures. We found that they can decouple metabolic rate and heart rate from body temperature: they maintained an extremely low metabolism and heart rate when exposed to ambient temperatures changing from 0 to 32.5 °C, irrespective of reproductive status. When we simulated natural temperature conditions, all non-reproductive bats used torpor throughout the experiment. Pregnant bats used variable strategies from torpor, to maintaining normothermy, or a combination of both. Even a short torpor bout during the day saved up to 33% of the bats' total energy expenditure. Especially at higher temperatures, heart rate was a much better predictor of metabolic rate than skin temperature. We suggest that the capability to flexibly save energy across a range of ambient temperatures within and between reproductive states may be an important ability of these bats and possibly other temperate-zone heterotherms.